Reflecting on the study of mobile collocated interactions: the changing face of wearable devices - Porcheron, Martin (2015)
Wearables, unlike smartphones, typically afford increasingly private or discrete interactions that are invisible to the casual observer. This shifting paradigm of device interaction combined with the increasing popularity of wearables presents an exciting opportunity for researchers to reflect on existing qualitative methodologies employed in observational studies of mobile collocated interactions, and how these can be adapted to the changing landscape of techno- logical interaction. This position paper discusses some of these methodologies, and questions the suitability of these approaches with respect to the changing form that devices can take.